Inheritance of a paternal ABCC8 variant and maternal loss of heterozygosity at 11p15 retrospectively unmasks the etiology in a case of Congenital hyperinsulinism - Caroline M. Joyce; Jayne A. Houghton; Domhnall J. O’Halloran; Paula M. O’Shea; Susan M. O’Connell (Clinical Case Reports, 2020)
Abstract Advances in genomics and 18F‐DOPA PET‐CT imaging have transformed the management of infants with Congenital Hyperinsulinism. Preoperative diagnosis of focal hyperinsulinism permits limited pancreatectomy with improved clinical outcomes while knowledge of the molecular etiology informs genetic counseling and provides a more accurate recurrence risk to families.